2016
DOI: 10.1172/jci82655
|View full text |Cite
|
Sign up to set email alerts
|

Loss of gastrokine-2 drives premalignant gastric inflammation and tumor progression

Abstract: Chronic mucosal inflammation is associated with a greater risk of gastric cancer (GC) and, therefore, requires tight control by suppressive counter mechanisms. Gastrokine-2 (GKN2) belongs to a family of secreted proteins expressed within normal gastric mucosal cells. GKN2 expression is frequently lost during GC progression, suggesting an inhibitory role; however, a causal link remains unsubstantiated. Here, we developed Gkn2 knockout and transgenic overexpressing mice to investigate the functional impact of GK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 66 publications
4
52
0
Order By: Relevance
“…1b, c, Supplementary Figure S1 in the ESM). These results are consistent with those of previous studies reporting that GKN2 alone does not affect cell growth [15] and that GKN2 −/− mice show no evidence of significant epithelial hyperplasia or spontaneous gastric tumors [20]. Thus, GKN2 may be able to acquire growth-inhibiting properties by interacting with TFF1, thereby facilitating the antiproliferative impact of the latter.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…1b, c, Supplementary Figure S1 in the ESM). These results are consistent with those of previous studies reporting that GKN2 alone does not affect cell growth [15] and that GKN2 −/− mice show no evidence of significant epithelial hyperplasia or spontaneous gastric tumors [20]. Thus, GKN2 may be able to acquire growth-inhibiting properties by interacting with TFF1, thereby facilitating the antiproliferative impact of the latter.…”
Section: Discussionsupporting
confidence: 92%
“…It seems that GKN2, when acting as a protein partner to TFF1, may be involved in the regulation of important anticarcinogenic effects of TFF1. Although GKN2 has been identified as a gastric tumor suppressor [19, 20], the precise roles of GKN2 alone and when interacting with TFF1 are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The heterodimeric interaction between GKN2 and TFF1 played an important in inhibition of GC [29]; thereafter, its anti-proliferative and pro-apoptotic effects on GC cells were further substantiated and other mechanisms of GKN2 action emerged [30], including the recent indication that GKN2 functions as a GKN1 inhibitor, contributing to the homeostasis of gastric mucosa. GKN2 also play a significant role in regulation of gastric inflammation [31].…”
Section: Discussionmentioning
confidence: 99%
“…Gastrokine-2 (GKN2) was shown to have an anti-inflammatory function and involvement in the regulation of mucosal Th1 responses. 16 Th1 cells and gastric pathology were increased in H. pylori-infected Gkn2 −/− mice, while innate immunity was dysregulated and myeloid suppressor cell responses reduced. In contrast, Yao et al 17 reported that H. pylori-upregulated expression of serum and glucocorticoidinducible kinase 1, induces Th17 and Th2 differentiation and reduces Th1 responses.…”
Section: T Cells and Cytokinesmentioning
confidence: 96%
“…H. pylori persists by manipulating this response; however, the underlying mechanisms are not fully understood. Gastrokine‐2 (GKN2) was shown to have an anti‐inflammatory function and involvement in the regulation of mucosal Th1 responses . Th1 cells and gastric pathology were increased in H. pylori ‐infected Gkn2 −/− mice, while innate immunity was dysregulated and myeloid suppressor cell responses reduced.…”
Section: Immunologymentioning
confidence: 99%